Active Packaging Film of Starch and Chitosan Incorporated with Beetroot Extract for Improvement of Quality and Shelf Life of Chicken Patties - Yadav, Vishwa Jeet; Shukla, V. H.; Zende, R. J. (Journal of Meat Science, 2022)
The present work evaluated the effect of edible film of starch and chitosan incorporated with beetroot extract on improving chicken patties’ quality and shelf life. The chicken patties coated with an edible film of starch and chitosan (T1) and chicken patties coated with an edible film of starch and chitosan incorporated with beetroot extract (T2) were compared with patties without any coating (control). The results revealed that T2 had significantly lower (P<0.05) pH, TBARS value, tyrosine value, and DPPH free radical scavenging activity than T1 and control during a storage period of 20 days. Total plate count, yeast and mold count, and psychrophilic counts were significantly reduced in T2 than in T1 and control, while coliforms were absent in all the treatments throughout the storage period. Edible film coating did not show any significant effect (P>0.05) on the sensory characteristics of patties during storage. The application of starch-chitosan edible film and beetroot extract extended chicken patties’ shelf-life by 8 to 10 days.